The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1002/marc.1995.030160706
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of ethylene over metallocenes confined inside the supercage of a NaY zeolite

Abstract: Metallocene catalysts entrapped inside the supercages of NaY zeolite were prepared by reacting NaY with methylaluminoxane (MAO) or trimethylaluminium (TMA) and then with Cp2ZrCI, (Cp: cyclopentadienyl) or Cp2TiCI2. NaY/MAO/Cp,ZrCl, and NaY/MAO/ Cp,TiCI, catalysts could polymerize ethylene. The amount of additional MA0 for the polymerization was lowered to a mole ratio of AVZr of 186. Molecular weights and melting points of polyethylene polymerized with Nay-supported catalysts were higher than those of polyethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 7 publications
1
23
0
1
Order By: Relevance
“…Catalysts B, c , D, active without cocatalyst (Tab. 1, runs 5, 8,11), exhibited much more steady kinetics, although the activities were sufficiently lower. In presence of M A 0 the activity of catalyst B was much lower than that of catalyst A (Tab.…”
Section: Resultsmentioning
confidence: 99%
“…Catalysts B, c , D, active without cocatalyst (Tab. 1, runs 5, 8,11), exhibited much more steady kinetics, although the activities were sufficiently lower. In presence of M A 0 the activity of catalyst B was much lower than that of catalyst A (Tab.…”
Section: Resultsmentioning
confidence: 99%
“…The immobilization of metallocene/MAO systems on solid carriers is normally accompanied by a decrease in catalytic activity. The activity drop has been attributed to (1) geometric restrictions of monomer access to the active sites 1,2 or the limitation of metallocene-MAO interaction due to isolated confinement; 3 (2) the deactivation of metal centers during the immobilization, which results in low ratios of activeto-total transition metal centers; 4,5 and (3) a decrease in the propagation rate. 6 Occasionally, supported metallocene/MAO catalysts exhibit higher average activities than homogeneous ones due to more stable kinetic profiles.…”
Section: Introductionmentioning
confidence: 98%
“…The activity of the heterogeneous catalyst is about 50-70% of its homogeneous catalyst under the same conditions (entry No 19,20,14,21) in Table IV, and this is a well-known phenomenon 27,[37][38][39][40] in olefin polymerization using supported catalyst and believed to be due to steric effects exerted by support on catalyst active centers, thus limiting the monomer incorporation ability. However, comparing entries 19 and 20, we observed that the molar mass of the polynorbornene obtained with SNC-6 was around two times higher than that obtained with the homogeneous catalyst 1.…”
Section: Effects Of Polymerization Conditions On Catalyst Activity Anmentioning
confidence: 94%